An institution-based process to ensure clinical software quality. - Abookire, S. A. (American Medical Informatics Association, 1999)
Clinical software can have a major impact on the delivery of care. It is imperative that clinical software undergo regular quality review, to evaluate the clinical correctness of the specification, the technical correctness of the software, problems that have arisen, and maintenance of the software as conditions change. We have developed a process using existing hospital review groups to perform clinical review, and using a project specification form and analysis of likely problem areas to effect technical review.